The observation of rock behaviour in uniaxial compression test (stress-strain curve) of limestone / Noor Juziana Johari - Johari, Noor Juziana (2006)
This study presents the results of laboratory testing of sedimentary rocks under uniaxial loading as well as in uniaxial compression test. The uniaxial compressive strength of a rock is one of the simplest measures of strength to obtain. It may be regarded as the highest stress that a rock specimen can carry when a unidirectional stress is applied, normally in an axial direction, to the ends of a cylindrical specimen. In other words the uniaxial compressive strength represents the maximum load supported by the specimen during the test divided by the cross-sectional area of the specimen. Laboratory rock testing is performed to determine the strength, engineering properties and the behaviour of fresh limestone. Fresh limestone was collected from Minerals and Geo-science Department Malaysia. Twenty samples have been prepared for the Uniaxial Compression Test on the fresh limestone. The laboratory performed of physical properties covered density, moisture content, Specific Gravity and porosity. It is also performed of dynamic properties covered Young’s Modulus and Poisson’s Ratio. From laboratory performance the Uniaxial Compressive Strength for limestone is between 44.03 MPa to 176.10 MPa respectively. For the engineering properties, it found that the mean of Young’s Modulus and Poisson’s Ratio are 63.66 GPa and 0.26 respectively. The behaviour of rock in uniaxial compression is influenced to some extent by the test conditions. From the deformation characteristics of limestone in Uniaxial Compression test, it was found that most of the deformation characteristic is in elastic deformation.